Ageing, Health, Loneliness and Wellbeing - Massimiliano Tani; Zhiming Cheng; Matloob Piracha; Ben Wang (Institute of Labor Economics (IZA), 2020)
Older people experience high rates of depression and suicide, yet they make a positive net contribution to the economy through activities such as employment, volunteering, and looking after grandchildren. The wellbeing of older people is therefore important not only on moral but also economic grounds. To understand which policies will facilitate the overall wellbeing, we use Australian data to explore the determinants of wellbeing and loneliness of natives and migrants in the 65-85 age group, taking into account the extent to which social networks contribute to the wellbeing and possible reduction in loneliness. Results show that social networks have a strong positive effect on wellbeing and a strong effect in reducing loneliness among both natives and migrants. The positive effect of social networks is stronger for females than males.
Keywords: I31; J14; 330; ageing; wellbeing; loneliness; social networks